Le divorce - Johnson, Diane (Dutton, 1997)
A witty look at French and American cultures. It begins when an American woman arrives in Paris to help her sister divorce an aristocratic husband who has taken off with another woman. The couple have a child and the two families, French and American, clash over its future. By the author of Persian Nights.
Keywords: Americans -- France -- Fiction; Divorce -- Fiction; Sisters -- Fiction; Frankreich; Paris (France) -- Fiction; Fiktionale Darstellung; Domestic fiction; Love stories